Pyoderma gangrenosum following surgical treatment of distal humerus fracture; A case report - Seyyed-Ramin Etemadi; Maryam Sedaghatnia; Seyyed-Mohsen Hosseininejad; Saeed Kokly (Journal of Orthopaedic Reports, 2024)
Background: Pyoderma gangrenosum (PG) is a rare noninfectious ulcerative disease that mimics infection but its etiology is unknown. Although it most commonly occurs after breast surgeries, it can also occur in orthopedic surgeries. If misdiagnosed, there is a risk of serious complications due to inappropriate or delayed treatment. Unlike infections, it must be treated with corticosteroids, and debridement is absolutely contraindicated. In the case of an early superficial pustular lesion that spreads rapidly despite properly administered antibiotic therapy, it is essential to keep an eye on the diagnosis. The detailed diagnostic factors and treatment options in our case are listed in this report. Case presentation: We report a case of PG after surgical treatment of a distal humerus fracture in a 40-year-old woman. She was misdiagnosed and underwent multiple debridement. After further investigation and diagnosis of PG, corticosteroid therapy was administered that improved her condition. Conclusion: It is important to pay attention to the timely diagnosis and intervention of PG to reduce the patients’ complications as well as prevent prolonged hospitalization and morbidity.